2020
DOI: 10.3389/fnagi.2020.580609
|View full text |Cite
|
Sign up to set email alerts
|

Face Recognition Deficits in a Patient With Alzheimer's Disease: Amnesia or Agnosia? The Importance of Electrophysiological Markers for Differential Diagnosis

Abstract: Face recognition deficits are frequently reported in Alzheimer's disease (AD) and often attributed to memory impairment. However, it has been hypothesized that failure in identifying familiar people could also be due to deficits in higher-level perceptual processes, since there is evidence showing a reduced inversion effect for faces but not for cars in AD. To address the involvement of these higher processes, we investigated event-related potential (ERP) neural correlates of faces in a patient with AD showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
2
5
0
Order By: Relevance
“…Consistent with the neuroimaging findings above, a lot of studies have shown that memory of unfamiliar faces and recognition of facial expressions skills are impaired in AD (Güntekin et al., 2019 ; Lavallée et al., 2016 ; Mazzi et al., 2020 ; Seelye et al., 2009 ; Spoletini et al., 2008 ; Werheid & Clare, 2007 ). In addition, poor face memory and recognition of facial expression performance have been demonstrated in patients with aMCI (Kawagoe et al., 2017 ; Nguyen et al., 2014 ; Seelye et al., 2009 ; Teng et al., 2007 ).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent with the neuroimaging findings above, a lot of studies have shown that memory of unfamiliar faces and recognition of facial expressions skills are impaired in AD (Güntekin et al., 2019 ; Lavallée et al., 2016 ; Mazzi et al., 2020 ; Seelye et al., 2009 ; Spoletini et al., 2008 ; Werheid & Clare, 2007 ). In addition, poor face memory and recognition of facial expression performance have been demonstrated in patients with aMCI (Kawagoe et al., 2017 ; Nguyen et al., 2014 ; Seelye et al., 2009 ; Teng et al., 2007 ).…”
Section: Introductionsupporting
confidence: 59%
“…Although the eye is the most important part of the face, in our study, a decrease was found in the number of fixations and the duration of of AD (Güntekin et al, 2019;Lavallée et al, 2016;Mazzi et al, 2020;Seelye et al, 2009;Spoletini et al, 2008;Werheid & Clare, 2007). These impairments may be related to the inefficient face-scanning found in our study.…”
Section: Discussionsupporting
confidence: 42%
“…Besides problems in cognitive functions including memory, attention, and orientation, patients with dementia often experience behavioral and psychological symptoms [ 9 ]. These include problems with face recognition [ 10 ], emotion recognition [ 11 ], apathy [ 12 ], and social functioning in everyday situations (e.g., initiating contact, expressing opinions) [ 11 ]. Thus, aberrant social behavior is both a risk factor and a symptom of AD.…”
Section: Introductionmentioning
confidence: 99%
“…AD is characterized by memory loss, agnosia, apraxia, aphasia, degradation of personality, loss of regulation of vital functions, and finally infectious disease leading to death in these patients. [2][3][4][5][6][7][8] Nearly 121 499 people died in AD due to complications in 2019. [1] The emergence of AD is reported to be associated with multiple risk factors including genetic and environmental sources, with progressing age being the most significant among them.…”
mentioning
confidence: 99%